Tubal Hydatidiform Mole: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
The incidence of ectopic pregnancy is 20 per 1,000 pregnancies. Hydatidiform mole occurs in 1 per 1,000 pregnancies. Thus, the incidence of the ectopic molar gestation is very rare. We report a case of tubal molar pregnancy diagnosed at the systematic histology examination of an ectopic pregnancy. A 22 years old second gravida presented with five weeks amenorrhea, severe lower abdominal pain and mild vaginal bleeding for one day; and excessive sweating and restlessness for 6 hours. On clinical examination, she had severe anaemia, pulse was 120 per minute and blood pressure was 80/60 mm hg. The gynecological examination was difficult because of lower abdominal pain and tenderness. She was diagnosed as a case of ruptured tubal pregnancy with shock. Pelvic ultrasound revealed an irregular echogenic mass in the left adnexa. She was resuscitated and emergency laparotomy was done: it revealed a left-sided ruptured ampullary ectopic pregnancy. Left salpingectomy was performed. The systematic histologic test identified an ectopic molar pregnancy. The patient was followed with weekly quantitative B-hCG titers until three successive B-hCG levels were negative. It is important that clinicians routinely send for histological examination of tubal specimens in ectopic pregnancy in order to diagnose cases of ectopic molar gestations early and provide appropriate post treatment follow up.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 104-106